Young people as a user of Tik Tok: creative works and entertainment connoisseurs - Albert Octavio Setiawan (The Indonesian Journal of Communication Studies, 2022)
Social media has expanded since globalization and digitization. This causes social media to become a place for every generation to enjoy entertainment or create entertainment itself. Some of the social media currently available are Facebook, Instagram, TikTok, and others. These three social media have something in common, providing entertainment in the form of short videos. Tiktok is one of the social media applications on the rise and invites application users to be creative when creating content in the form of videos. Someone who was previously unknown to many people in the TikTok application becomes an influencer or public figure if the audience of the TikTok application likes the videos or the work of the video maker. Researchers will use descriptive qualitative methods by interviewing three sources whose have different backgrounds. By using the theory of use and gratification, researchers will see that the TikTok application connoisseur and the creator of the uploading works have a satisfying effect when watching or seeing good feedback from the audience of the application.